Rispinge : alde en nije fersen - Troelstra, Pieter Jelles (Den Haag : De Atlas, 1909)
Bibliotheek Camille Huysmans
Dedicator: Troelstra, Pieter Jelles, dedicatee: Huysmans, Camille
Fries
Monografie
Keywords: poëzie